Answer:
4y = -3x - 48
Step-by-step explanation:
y - y1 = m(x - x1)
y1 = -9 x1= -4 m = -3/4
y -(-9) = -3/4(x -(-4)
y + 9 = -3/4(x + 4)
y + 9 = -3/4x -12/4
multiply through by 4
4y + 36 = -3x -12
4y = -3x -12-36
4y = -3x -48 in the form y = mx + c
Answer:
5(X+5x8)
Step-by-step explanation:
i hope this helpssss
True because you can put it in any order without affecting it. Example : 5 • 7 = 7 • 5. Either way they still equal 35, therefore the answer will be true.
Hope this helps :)
1/3 - 1/6
= 2/6 - 1/6
= 1/6
so, 1/3 - 1/6 = 1/6